PEMANFAATAN ABU GOSOK DAN KHITOSAN SEBAGAI UPAYA PENINGKATAN MUTU DAN EFESIENSI PADA PENGOLAHAN AGAR-AGAR KERTAS DI PAMEUNGPEUK, GARUT JAWA BARAT - Sugeng Heri Suseno (Jurnal Ilmu Pertanian Indonesia, 2006)
This study attempts to increase the quality and for production gelatinous paper that is by using ashes rub as a substitute for potassium hydroxide ( koh ) that serves as penjedal and khitosan to improve the quality of organoleptik from gelatin paper.The research obtained that treatment ashes rub 30 % and khitosan 0.6 % give the best results in the test gel strength compared to the, while in the color and texture not markedly dissimilar and control.